(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Health is wealth, everyone knows this fact but only few people follow. In today’s technological modern world, every person has become so busy that he does not have time for himself, he cannot take care of his health even if he wished. Today’s human is compelled that he will have to grow step by step with technology. So nowadays people have also given the responsibility of taking care of their health to the technology. In today’s time, humans have a lot of digital health care devices and their use is increasing due to lack of time. On the other hand, the use of these devices accumulates the patient’s own sensitive personal details, which can cause a great harm to the person due to misuse. In such a situation, only a strong law can help. Here, it is the responsibility of Indian law and order to prepare such a framework by which the sensitive personal data of the citizen is protected. Through this paper, it has been analyse how active the Indian Legislature is in this area and what it is trying to do